PENGARUH PEMBERDAYAAN DAN PEMBELAJARAN ORGANISASI TERHADAP KOMITMEN ORGANISASI DOSEN SEKOLAH TINGGI ILMU TARBIAH AL-AMIN, TANGERANG SELATAN - Lilis Sakuroh (Universitas Negeri Jakarta, 2016)
The purpose of this research is to determine the effect of empowerment and organizational learning on organizational commitment the Lecture STTI Al-Amin. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) organizational structure has a positive direct effect in productivity, (2) job design has a positive direct effect in productivity, (3) organizational structure has a positive direct effect in job design